2016
DOI: 10.1007/s00360-016-0997-x
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effects on Drosophila larva hearts: room temperature, acute and chronic cold stress

Abstract: Ectothermic animals are susceptible to temperature changes such as cold shock with seasons. To survive through a cold shock or season, ectotherms have developed unique strategies. Our interest is focusing on the modulation of physiological functions during cold shock and prolonged cold exposure in the fruit fly. We use Drosophila melanogaster as a model system to investigate cardiac function in response to modulators (5-HT-serotonin, Ach-acetylcholine, OA-octopamine, DA-dopamine and a cocktail of modulators) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 70 publications
1
11
0
1
Order By: Relevance
“…Based on these results, similar dependencies may also be observed in insects. This supposition is partially confirmed by the results of Zhu et al (2016) in a study on the D. melanogaster heart. The authors demonstrated a strong excitatory effect of biogenic amines on the larval heart during cold exposure but only in the case of 5-HT.…”
Section: Biogenic Aminessupporting
confidence: 55%
See 2 more Smart Citations
“…Based on these results, similar dependencies may also be observed in insects. This supposition is partially confirmed by the results of Zhu et al (2016) in a study on the D. melanogaster heart. The authors demonstrated a strong excitatory effect of biogenic amines on the larval heart during cold exposure but only in the case of 5-HT.…”
Section: Biogenic Aminessupporting
confidence: 55%
“…However, as suggested by Zhu et al (2016), different modes of action of OA at different temperatures may be related to the activation of different subunits of the G protein-coupled receptor. The Gαq subunit, whose activation evokes a positive chronotropic effect, is most likely suppressed, but Gαi-coupled receptors are activated, which may lead to the opposite effect of OA on insect heart during cold stress (Zhu et al, 2016). Generally, biogenic amines may be needed to maintain heart functioning during chronic exposure to cold.…”
Section: Biogenic Aminesmentioning
confidence: 97%
See 1 more Smart Citation
“…However, one needs to be cautious in relating changes in the compounds in the hemolymph to one condition such as exercise, environment, or stunning procedure, as these compounds can vary with a molt cycle, circadian cycle, gravid status, social dominance, and health of the animals [ 15 , 16 , 40 , 41 , 42 ]. Even insects show changes in levels of biogenic amines with environmental stressors and/or exercise [ 43 , 44 , 45 ]. In cold (10 °C) exposed Drosophila melanogaster both serotonin and octopamine concentrations decreased in the hemolymph [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to its success as a genetic model system, the minuteness of Drosophila challenges the methods used to quantify performance of its tubular heart. Various approaches have been employed that include manual counting of heart vessel contractions (Zhu et al, 2016), electrophysiological recordings of muscle potential (Johnson et al, 1998) and sophisticated optical methods (Klassen et al, 2017;Wasserthal, 2007;Wolf et al, 2006). A resilient compromise between instrumental costs on the one hand and the richness in detail of the data on the other hand has been the semiautomatic optical heartbeat analysis (SOHA) developed by Fink and Ocorr, which determines functional parameters of the fly tubular heart from high-speed digital video film (Cammarato et al, 2015;Fink et al, 2009).…”
Section: Introductionmentioning
confidence: 99%